Internal Limiting Membrane Flaps for Coexistent Macular Hole and Retinal Detachment in Eyes with Proliferative Diabetic Retinopathy - San-Ni Chen; Chung-May Yang (Journal of Ophthalmology)
Purpose. To evaluate logical surgical approaches to closing macular holes in eyes with proliferative diabetic retinopathy with retinal detachment. Methods. Retrospective, interventional case series. Results. 10 eyes in 10 patients were included in this study. The inverted internal limiting membrane (ILM) flap technique was used in 2 eyes, while inverted ILM insertion was used in 5 eyes, and free ILM flaps in 3 eyes. Closed macular holes and retinal reattachment were observed in all eyes. Best corrected visual acuity improved from 1.33 ± 0.39 preoperatively to 1.02 ± 0.36 postoperatively (p=0.03). Conclusion. Various surgical approaches utilized in managing macular holes may effectively close macular holes and reattach retinas. This trial is registered with NCT 03618498.